Agricultural Credit as a Driver for Rural Development: Analyzing the Nexus Between Micro-Credit Disbursement, Regional Economic Growth, and Poverty Alleviation - A. St. Fatmawaty; Riyanti Isaskar; Irvo Isaskar Mandang (Agriculture Journal, 2026)
The agricultural sector remains a vital rural economic pillar that is frequently hindered by restricted access to formal capital. This research seeks to evaluate the impact of micro-credit disbursement on agricultural RGDP growth and poverty reduction within the Indonesian context. Employing a quantitative research design with panel data from 38 provinces spanning the 2020–2025 period, the study processes official secondary data sourced from Statistics Indonesia, Bank Indonesia, and the Financial Services Authority. The analytical results demonstrate that a 15.00% annual expansion in micro-credit significantly stimulates an average base sector growth of 2.07% and effectively reduces rural poverty rates to a level of 11.74% as of 2024. Furthermore, these research findings underscore the decisive role of village infrastructure and financial digitalization in amplifying the effectiveness of disbursed capital. This study concludes that the integration of inclusive monetary policies with rural physical development constitutes a fundamental strategy for achieving resilient and inclusive agrarian economic transformation. Policy recommendations are directed toward strengthening credit guarantee systems and digitalizing farmer risk assessments to broaden the scope of financing without the burden of heavy physical collateral.